2018
DOI: 10.1097/ico.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Cross-Linking in Pediatric Patients: Evaluating Treated and Untreated Eyes—5-Year Follow-Up Results

Abstract: Our long-term follow-up study suggests that CXL is a safe procedure in the pediatric age, and there is no urgency in treating pediatric patients with keratoconus without proof of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
28
1
1
Order By: Relevance
“…Our results showed that the eyes remained stable with respect to Kmax 1 year after ATE-CXL when compared to the preoperative assessment, which may indicate that ATE-CXL is an effective treatment for halting the progression of pediatric keratoconus. Or et al ( 7 ) and Eissa et al ( 20 ) reported that Kmax remained stable 1 year after C-CXL and accelerated CXL (A-CXL) for pediatric patients with keratoconus, which was consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that the eyes remained stable with respect to Kmax 1 year after ATE-CXL when compared to the preoperative assessment, which may indicate that ATE-CXL is an effective treatment for halting the progression of pediatric keratoconus. Or et al ( 7 ) and Eissa et al ( 20 ) reported that Kmax remained stable 1 year after C-CXL and accelerated CXL (A-CXL) for pediatric patients with keratoconus, which was consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results suggested no significant changes in CCT, TCT, and AT 1 year after ATE-CXL, which indicated the efficacy of stabilizing the corneal thickness in pediatric progressive keratoconus. Previous studies ( 6 , 7 , 21 ) assessing the C-CXL outcomes in pediatric patients with keratoconus reported a significant decrease in corneal thickness compared with preoperative results. In our study, the corneal thickness remained stable at each follow-up examination because the corneal epithelium was preserved during the operation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There is small amount of information about rate of progression of untreated keratoconus eye. Or et al 25 have demonstrated that in a 5 year follow-up there was no progression for untreated eyes served as control eyes for fellow treated eye. Wittig-Silva et al 26 also used the fellow untreated eye as a control group, but offered a compassionate treatment after enrollment, thus eliminating the chance to acquire progression data for untreated eye.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, la progresión del KC en los niños es agresiva y puede que no se detenga por sí sola 26,37,40 . Esto puede llevar a un deterioro visual progresivo en los pacientes pediátricos y afectar su desarrollo social y educativo y, por lo tanto, afectar negativamente a su calidad de vida 45,46 .…”
Section: Discussionunclassified